The Comparative Effectiveness of Angiotensin II Receptor Blockers and Angiotensin-Converting Enzyme Inhibitors in Outpatient Hypertensive Patients at Community Health Centers - Prasetyawan, Fendy; Yuneka Saristiana; Faisal Akhmal Muslikh; Wisnu Haryo Widyoko; Chandra Arifin; Abd Rofiq (International Journal of Contemporary Sciences (IJCS), 2024)
Hypertension, often termed "The Silent Disease" due to its asymptomatic nature, remains a global health concern. This study investigates the comparative effectiveness of Angiotensin II Receptor Blockers (ARBs) and Angiotensin-Converting Enzyme Inhibitors (ACEIs) in managing hypertension, focusing on Valsartan and Candesartan (ARBs) and Ramipril and Captopril (ACEIs). Analyzing retrospective data from Community Health Centers in Solo City, the research aims to provide nuanced insights into outpatient care scenarios. The meticulous statistical analysis, utilizing SPSS and t-tests, uncovers notable differences, particularly favoring Valsartan and Ramipril within their respective drug classes. These findings carry substantial implications for healthcare practitioners, aiding in the development of precise treatment guidelines. Understanding the comparative clinical effectiveness, safety profiles, and tolerability of ARBs and ACEIs ensures a more personalized approach to hypertension management